Effect of low-dose blanched Saccharina latissima in finishing bulls’ diets on carcass and meat quality traits - Grabež, Vladana; Mydland, Liv Torunn; Papoutsis, Dimitrios; Øverland, Margareth; Egelandsdal, Bjørg (Frontiers in Animal Science, 2023)
Nutritional and bioactive compounds present in seaweeds makes them suitable supplements or feed ingredients in livestock diet. This study assessed the effect of blanched seaweed (Saccharina latissima) supplemented to finishing bull's diet on carcass traits and quality of the longissimus lumborum (LL) and semimembranosus (SM) muscles. The inclusion rate of 0.8% dry matter blanched S. latissima in bulls' diet was maximum allowed amount due to iodine and arsenic thresholds in animal feed. Nineteen Limousine crossbreed bulls were randomly assigned to two groups consisting of a control (CD, n = 9) diet or a test diet supplemented with blanched seaweed (SW, n = 10) and fed for 48 days pre-slaughter. Carcasses from bulls finished on seaweed supplemented diet had heavier (P < 0.05) weight than the control, while conformation and fatness were similar (P > 0.05). pH was lower (P < 0.05) in CD LL early postmortem than SW, while no differences (P > 0.05) were found in ultimate pH. Meat from both diets had similar (P > 0.05) drip loss and shear force at Day 7 and 14. Cooking loss at Day 7 was not affected (P > 0.05) by diet, while on Day 14 cooking loss was greater (P < 0.05) for SW than CD meat. Warmed-over flavor and shear force were muscle dependent; lower (P < 0.05) for LL than SM. Seaweed supplementation to finishing bull's diet had no clear effect on color changes (L*, a*, and b* values) during chilled storage, although reduced b* values (P < 0.05) suggested improved color stability of meat from SW compared to CD fed animals. Iodine content was higher (P < 0.05) in the SW meat than CD even when using the low seaweed supplementation level requested by the authorities. A small increase of Deleted: beef 38 Deleted:This is a provisional file, not the final typeset article arsenic in meat with seaweed supplementation has no implications on human health. Cost-efficient processing methods for further reduction of iodine and arsenic are needed to increase utilization of seaweed as a feed additive/ingredient and attain a clear effect on meat quality.